Social construction as postmodern discourse: An epistemology for conversational therapeutic practice - E Kotzé; DJ Kotzé (Acta Theologica)
Social contstruction discourse is a postmodern approach that provides a meaningful epistemology for therapies using conversation as a means to help people. Knowledge is viewed as a result of a social process and not as the objective description of external realities. Language provides the parameters for our understanding and experience. Discourse and language are discussed, as well as how people's lives and relationships are constituted by the dominant discourses of society. The deconstruction of power through reflecting conversation and transparancy practices is attended to.